BINA SUASANA SEBAGAI UPAYA PENCEGAHAN PENYALAHGUNAAN NARKOBA DI SMA SEDERAJAT KOTA SURABAYA - Fitriana, Jeni Martiyanti (Fakultas Kesehatan Masyarakat, Universitas Jember, 2019)
The high rate of drug abuse in Indonesia has spread to high school adolescents. 183 million people consume marijuana, 35 million opioids, 37 million amphetamines and drug stimuli, 22 million ecstasy, 18 million opiates, 17 million kokai (BNN, 2017). East Java is one of the provinces where the population is at risk of experiencing drug abuse. Surabaya occupies a position as a metrapolitan city which has a high level of modernity both from technology and infrastructure. The high level of population and technological advances have made this region vulnerable to drug abuse. The role of the School is to develop capabilities and shape dignified national character and civilization in order to educate the life of the nation and the state aimed at developing potential students to become human beings who believe and fear God Almighty, noble, healthy, knowledgeable, capable, creative , be independent, and become a democratic and responsible citizen. For this reason, schools have an important role related to the prevention of drug abuse. Based on the data and policies obtained, the researchers aimed to identify the atmosphere development strategy in schools in an effort to prevent drug abuse in schools. This research was conducted using in-depth interviews with 14 informants who held positions as teachers. The research conducted will later use the WHO 1984 Health Promotion Strategy approach by using atmosphere development variables. The results of the study stated that the community development activities carried out in North Surabaya's high schools were in the form of peer counselors, teaching and learning activities, inspection, urine tests and counseling facilities.